RUTA TURÍSTICA CULTURAL DEL CANTON CELICA, PROVINCIA DE LOJA - Chamba Salazar, Vicente Vinicio (2015)
The Celica Canton is located 165 km from the city of Loja a captured city of green mountains, different climatic zones, lush and varied agriculture livestock, founded by the Indians who were older than the Incas. It also has a variety of natural and cultural attractions is why we allowed for the present research, for which the overall objective was raised: "Develop a Tourist Route Cultural attraction Canton Celica, Loja Province" to develop the general objective, three specific objectives will be plated: the first "Making the tourist diagnosis of the current situation of Canton Celica, Loja Province" to achieve this objective methods was used as the analytical, synthetic, inductive ; techniques of direct observation and interview; materials (office supplies, bibliographic and technological) tools and the SWOT matrix; Diagnostic tab Tourist Community of Carla Ricaurte, inventory records and ranking MINTUR (Ministry of Tourism of Ecuador), necessary supplies to collect the necessary information so we can determine the current status of the canton. The second objective: "To propose designing the tourist route to the authorities of the Canton Municipal GAD Celica" instruments like GPS was used to collect georeferenced points every Attraction, allowing determine the exact position of the same The matrix to validate tourist routes served to determine important aspects such as: general route data and information that will help the economy and the development of it. At the end with the collected data and presentation of the final photographs cuadriptico where terrestrial distances, pictograms attraction, support services and tourism, representative photographs of the site, logo Canton and detailed tour route was made; on the back of information from each Attraction is to complement a tourist route and itinerary was prepared script. The third objective: "Socialize the proposal of the tourist route to the authorities and the general community of Canton Celica" was developed in three phases. The first phase, by convening the authorities and the people involved in tourism, the second phase, presentation of the results obtained in this research, where the third phase took different conclusions and recommendations of the proposal. The final result is determined that the Cultural Tourism Route "full of charm Celica Earth" will be a very important tourism development in the canton factor. We conclude that this research is very important because it will allow natural and cultural tourist attractions are known to local, provincial and national level will also allow linking with the public to integrate the tourist activity; basic services are not suitable for the reception of tourists, promotion and dissemination by the authorities in power will be very important as it will allow the development of cultural tourism. The main recommendations are: work together with the Ministry of Tourism of Ecuador for this paper the run, as it will be very important to improve the quality of life of the inhabitants; and whether Canton Tourism Development also promote and disseminate this Cultural Tourist Route at local, provincial and national levels. Likewise, local authorities continuously provide courses to owners of tourism enterprises for infrastructure and quality services for tourists visiting future improvement.